Nutrient-Induced Inflammation in Polycystic Ovary Syndrome: Role in the Development of Metabolic Aberration and Ovarian Dysfunction - González, Frank (Seminars in Reproductive Medicine, 2015)
A pathophysiology paradigm shift has emerged with the discovery that polycystic ovary syndrome (PCOS) is a proinflammatory state. Despite the dogma that the compensatory hyperinsulinemia of insulin resistance is the promoter of hyperandrogenism, physiological insulin infusion has no effect on androgen levels in PCOS. The dogma also does not explain the cause of hyperandrogenism and ovarian dysfunction in the 30 to 50% of women with PCOS who are of normal weight and lack insulin resistance. Inflammation is the underpinning of insulin resistance in obesity and type 2 diabetes, and may also be the cause of insulin resistance when present in PCOS. The origin of inflammation in PCOS has been ascribed to excess abdominal adiposity or frank obesity. However, nutrients such as glucose and saturated fat can incite inflammation from circulating mononuclear cells (MNC) of women with PCOS independent of excess adiposity and insulin resistance, and can also promote atherogenesis. Hyperandrogenism activates MNC in the fasting state to increase MNC sensitivity to nutrients, and is a potential mechanism for initiating inflammation in PCOS. However, chronic ovarian androgen suppression does not reduce inflammation in normal-weight women with PCOS. Direct exposure of ovarian theca cells to proinflammatory stimuli in vitro increases androgen production. These findings may be corroborated in vivo with anti-inflammatory therapy to normal-weight insulin-sensitive women with PCOS without abdominal adiposity to observe for amelioration of ovarian dysfunction.
Keywords: hyperandrogenism; inflammation; oxidative stress; insulin resistance; abdominal adiposity